Paraproteinemic neuropathy: a practical review. Issue 1 (December 2016) - Rison, Richard; Beydoun, Said
Abstract The term paraproteinemic neuropathy describes a heterogeneous set of neuropathies characterized by the presence of homogeneous immunoglobulin in the serum. An abnormal clonal proliferation of B-lymphocytes or plasma cells, which may or may not occur in the context of a hematologic malignancy, produces the immunoglobulins in excess. If malignancy is identified, treatment should be targeted to the neoplasm. Most cases, however, occur as monoclonal gammopathy of undetermined significance. Few prospective, randomized, placebo-controlled trials are available to inform the management of paraproteinemic neuropathies. Clinical experience combined with data from smaller, uncontrolled studies provide a basis for recommendations, which depend on the specific clinical setting in which the paraprotein occurs. In this review, we provide a clinically practical approach to diagnosis and management of such patients.